ONLINE MARKETING DALAM KOMUNIKASI PEMASARAN PULSA ELEKTRIK DI KIOS CELL KOTA BENGKULU - Efri Agus; Vethy Octaviani; Yusuarsono Yusuarsono (UNIVED PRESS, Universitas Dehasen Bengkulu, 2018)
According to research it is obtained: attention, interesting display and pictures of electric balance which can attract customer and make them interest to try and top-up balance because the transaction is fast, easy on delivery and cheap also various model which displayed. Society can also a new agent, kios cell open for 24 hours so customer can always be served. Interest because of online advertisement by showing the price is cheaper than other sellers, but the problem comes from internet connection so it delays in sending the electric balance. Desire is still in customer who being aware in top-up electric balance with online media, cheap and fast in every transaction makes customers satisfy. The loss when sending the balance get delayed so that account will use personal balance which caused the customer loss. Action of kios cell owner can give a guidance through brochure and give direct guidance to customer about how to do a transaction in purchasing electric balance through facebook or token.